State-owned enterprises in Africa and the economics of public service delivery - Abioro, 'Tunde A. (AOSIS, 2022)
This book intends to provide a continuous assessment of the crisis in governance in Africa. As it is, there are huge deficits in the capacity of African states to harness vast human and material resources to promote good governance. This manifests in pervasive corruption, collapsed service delivery, collapsed state-owned enterprises, eroded social trust, capital flight, escalating levels of poverty and wars, human insecurity, and stunted growth. The public sector is the pulse of service delivery because the entire governance system revolves around the sourcing of materials and services, mostly from the private sector, in order to achieve its public policy intents. The procurement process, therefore, ordinarily ought to yield positive economic outcomes and an efficiency-driven system in favour of the government itself and its service recipients. However, this more often than not is not the case. Despite its enormous wealth, the African continent is in an economic quagmire, a dilemma that requires multi-facet research activities. This is the motivation for this book.